2011
DOI: 10.1039/c0ob01088j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient iron-mediated approach to pyrano[3,2-a]carbazole alkaloids—first total syntheses of O-methylmurrayamine A and 7-methoxymurrayacine, first asymmetric synthesis and assignment of the absolute configuration of (−)-trans-dihydroxygirinimbine

Abstract: Iron-mediated oxidative cyclisation provides an efficient approach to pyrano[3,2-a]carbazole alkaloids. Thus, improved routes to girinimbine and murrayacine as well as the first total syntheses of O-methylmurrayamine A and 7-methoxymurrayacine are reported. Asymmetric epoxidation of girinimbine led to (-)-trans-dihydroxygirinimbine and the assignment of its absolute configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…This second approach started with the oxidation of 9 a by using DDQ to obtain the corresponding aldehyde murrayacine ( 24 ) in 96 % yield (Scheme ) . Boc‐Protection of the carbazole nitrogen atom of 24 followed by reduction of the carbaldehyde to a hydroxymethyl group and activation of the latter as para ‐nitrobenzoate provided 25 in 87 % yield over three steps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This second approach started with the oxidation of 9 a by using DDQ to obtain the corresponding aldehyde murrayacine ( 24 ) in 96 % yield (Scheme ) . Boc‐Protection of the carbazole nitrogen atom of 24 followed by reduction of the carbaldehyde to a hydroxymethyl group and activation of the latter as para ‐nitrobenzoate provided 25 in 87 % yield over three steps.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the same alkaloid was also obtained by others and several synthetic approaches have been developed. We applied a molybdenum‐mediated, an iron‐mediated, and our palladium‐catalysed route to the synthesis of 9 a ,. (+)‐Mahanimbine ((+) ‐9 b ) was isolated for the first time in 1966 by Chakraborty et al.…”
Section: Introductionmentioning
confidence: 99%
“…Under optimized conditions (excess of titanium(IV) tetraisopropoxide), the reaction with 1 led to 3 in 82 % yield (Scheme ). Our three previous approaches to this natural product, all using 5‐amino‐2,2,8‐trimethylaminochromene as building block, provided 3 either via a molybdenum‐mediated synthesis (2 steps, 11 % overall yield),29b a palladium‐catalyzed process (3 steps, 26 % overall yield),30l or an iron‐mediated approach (2 steps, 58 % overall yield) 35. The present route via a palladium‐catalyzed synthesis of 1 and subsequent annulation of the pyran ring affords 3 in 4 steps and 69 % overall yield based on 3‐methoxy‐4‐methylaniline and currently represents the best approach.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation with 2,3‐dichloro‐5,6‐dicyano‐1,4‐benzoquinone (DDQ) using a mixture of methanol, tetrahydrofuran, and water as solvent provided 4 in an improved yield (96 %). In a previous study in cooperation with the group of Professor Katsuki (Kyushu University, Fukuoka, Japan), we have shown that 3 can be transformed into natural (−)‐ trans ‐dihydroxygirinimbine ( 22 ) via asymmetric epoxidation and subsequent hydrolysis (98 % ee ) 35. 36…”
Section: Resultsmentioning
confidence: 99%
“…54 The high synthetic utility was further demonstrated by Kishi, 55 Fürstner, 56 and Knölker, 57 who each employed the Ti(Oi-Pr) 4 /K7 R /H 2 O 2 system to prepare a chiral epoxide as the building block for the synthesis of their target natural products, respectively (Scheme 23).…”
Section: B53mentioning
confidence: 99%